Anti-diabetic activity and mineral elements evaluation of vernonia amygdalina leaves obtained from Malaysia - Alara, Oluwaseun Ruth; Nour, A. H. (Marmara University, 2019)
Diabetes has been characterized by transmuted lipids, hyperglycemia, proteins, and carbohydrates metabolism that can affect the quality of life. Although there are quite several synthetic drugs used in managing this disease, however, due to their side effects, the use of natural sources is imperative. This study focused on the in-vitro inhibitory activity of Vernonia amygdalina leaf grown in Malaysia using both α-amylase and α-glucosidase assays. The quantities of mineral elements in the plant extracts through microwave-assisted and Soxhlet extraction methods were as well examined through inductively coupled plasma mass spectrometry (ICP-MS) analysis. The extract of V. amygdalina leaf showed the highest dose-dependent effect of 97.28 and 98.08% of inhibition at 1.0 mg/mL having IC50 values of 0.51 mg/mL and 0.49 mg/mL against α-amylase and α-glucosidase enzymes, respectively. The inhibitory effects of the extract were higher than acarbose (a standard drug). Moreover, the results showed that higher quantities of mineral elements (potassium, magnesium, and calcium) and a lesser quantity of chromium in the extracts through microwave-assisted extraction (MAE) indicate that the technique possesses a higher capacity in obtaining higher mineral nutrients over Soxhlet extraction and more anti-diabetic activity of the extract. Thus, the extract exhibited an effective anti-diabetic activity which implies that it potentially serves as a natural source for managing diabetes.